Detection of Escherichia Coli Using PCR Analysis Without DNA Extraction - Widodo, Wimbuh Tri; Huda, Choirul (Folia Medica Indonesiana, 2021)
This study aimed to detect Escherichia coli directly without DNA extraction. The nucleus membrane and cell membranes of the Escherichia coli are composed of a phospholipid bilayer, damaged if heated at 950C. Pre-denaturation and denaturation of PCR were carried out at 950C. The two stages are thought to break down the Escherichia coli cells, so that the DNA that comes out of the cells can directly become a template in the PCR analysis. In this study, PCR analysis was carried out using Escherichia coli culture, Escherichia coli bacteria culture incubated at 950C, and Escherichia coli bacteria cultures incubated at 650C + on ice as templates. The results showed that PCR analysis using Escherichia coli culture directly and Escherichia coli culture incubated at 650C + on ice as templates produced very thin DNA bands with a size of 580 bp. while PCR analysis using Escherichia coli bacteria culture incubated at 950C as a template produced thick DNA bands with a size of 580 bp. This study's results are very useful for saving time and costs in the detection of Escherichia coli bacteria. The sample to be tested does not need DNA isolation as usual, but only needs to be incubated at 950C for 10 minutes.